The Conversion of Iceland and the First Icelandic Bishops - DEL ZOTTO, Carla (Istituti Editoriali e Poligrafici Internazionali, 2011)
La conversione dell'Islanda medievale e la nascita della storiografia islandese. This article presents the history of the early Church of Iceland and investigates the early vernacular sources dedicated to the first bishops of Iceland.